Instagram Social Media Marketing Communication Performance Evaluation @Baturadenpalawi - Hidayah, Nurdin; Salsabila, Ramani Khalda; Saputra, Rizqi Anggie; Dewi, Elena Kartika; Jannatan, Muhammad Wildan; Nufus, Najiah Hayati; Fahriza, Audita; Monicawati, Syalsabilla (Integrasi Sains Media, 2023)
This research discusses the evaluation of marketing communication performance on Instagram by user @baturadenpalawi in Wana Wisata Baturaden (Baturraden District), Banyumas Regency, Central Java, Indonesia. The researcher used the Concept of Tourism Marketing Communication Objectives by Nurdin Hidayah to inform, persuade, and remind. The data was collected through observations, questionnaires, interviews, and documentation studies. Analysis, questionnaires, and interviews are used to obtain the results. This research leads to the evaluation of marketing communications and produces recommendations for each dimension (to inform, to persuade, and to remind) on Instagram account @baturadenpalawi.